Breast cancer in younger women in Switzerland 1996–2009: A longitudinal population-based study. Issue 2 (April 2015) - Bodmer, Alexandre; Feller, Anita; Bordoni, Andrea; Bouchardy, Christine; Dehler, Silvia; Ess, Silvia; Levi, Fabio; Konzelmann, Isabelle; Rapiti, Elisabetta; Steiner, Annik; Clough-Gorr, Kerri M.; NICER Working Group, 2
Abstract Background Breast cancer (BC) is the most commonly diagnosed cancer and a leading cause of death in younger women. Methods We analysed incidence, mortality and relative survival (RS) in women with BC aged 20–49 years at diagnosis, between 1996 and 2009 in Switzerland. Trends are reported as estimated annual percentage changes (EAPC). Results Our findings confirm a slight increase in the incidence of BC in younger Swiss women during the period 1996–2009. The increase was largest in women aged 20–39 years (EAPC 1.8%). Mortality decreased in both age groups with similar EAPCs. Survival was lowest among women 20–39 years (10-year RS 73.4%). We observed no notable differences in stage of disease at diagnosis that might explain these differences. Conclusions The increased incidence and lower survival in younger women diagnosed with BC in Switzerland indicates possible differences in risk factors, tumour biology and treatment characteristics that require additional examination.